The Influence of Self-Control and Loneliness on Online Game Addiction at X Game Center Depok - Afiyah Ariqohsari Yaksan, Andi; Nadila Putri Faisah, Andi; Nurul Ainie, Azdira (Lafadz Jaya Publisher, 2024)
The rapid development of technology in this era of globalization has had a big impact, both positive and negative, on people's lives. The internet, which can be accessed easily, is often used to access various kinds of entertainment content, one of which is online games. Playing online games continuously will cause individuals to become addicted. This is due to low self-control, making it difficult for players to stop the habit of playing online games. Players who feel lonely also tend to experience addiction due to using online games as a means of coping with the feeling of loneliness they experience. This research is quantitative research using incidental sampling techniques on online game players at X Game Center Depok totaling 127 respondents. The measuring instruments used in this research refer to aspects of online game addiction according to Chen and Chang (2008), aspects of self-control according to Averill (2012), and aspects of loneliness according to Russell in the UCLA Loneliness Scale (1996). The three measuring instruments have been tested and the results are valid and reliable. The results of statistical analysis prove that there is a significant influence in a negative direction on self-control towards online game addiction. Furthermore, the results of statistical analysis also show that there is a significant influence in a positive direction on loneliness on online game addiction. For future researchers, it is recommended to use other variables such as self-esteem, environmental control and social relationships. Future researchers are also advised to conduct research in various different game centers so as to obtain more precise and extensive comparisons and results.